Les lieux communs du roman : stéréotypes grecs d'aventure et d'amour - Létoublon, Françoise, 1946- (Mnemosyne, Supplements, 1993)
The author uses an extensive study of the five Greek novels preserved by tradition since Roman times (Chariton, Chaireas and Callirhoe , Longus, Daphnis and Chloe , Xenophon of Ephesus, Ephesiaca , Achilles Tatius, Leucippe and Clitophon , Heliodorus, Ethiopica ) to show how the novel form, from its origins, has been based upon the repetition of commonplaces, τόποι, which allows an interplay with the reader. The commonest of these commonplaces, love-Eros, provides the plot of the five novels, in an order which is itself topical: meeting and love at first sight, wounds of love and lovesickness, lovers separated, lovers put to the test by the sea and by pirates, lovers reunited. The heroes of Greek novels, always young, good-looking and well-born (even if their identities are left unclear), allow for easy reader identification. From Xenophon of Ephesus (the most primitive form of the novel) to the Ethiopica (a true work of art), the Greek novel had already explored all the main narrative possibilities of the genre.